2010
DOI: 10.1603/en10016
|View full text |Cite
|
Sign up to set email alerts
|

Pheromonal Cross-Attraction in True Bugs (Heteroptera): Attraction of Piezodorus hybneri (Pentatomidae) to Its Pheromone Versus the Pheromone of Riptortus pedestris (Alydidae)

Abstract: We investigated the attractiveness of a synthetic form of the pheromone of the soybean stink bug, Piezodorus hybneri (Gmelin), under field conditions, and compared it with that of (E)-2-hexenyl (E)-2-hexenoate, a pheromone component of a competitor, Riptortus pedestris (Fabricius). Many adult stink bugs were attracted to traps baited with 100 mg of the synthetic pheromone (1: 1: one mixture of β-sesquiphellandrene, (R)-15-hexadecanolide, and methyl (Z)-8-hexadecenoate), but few were attracted to 1 or 10 mg. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Sex and aggregation pheromones have been identified in approximatively 50 species where the pattern of responses is divided between those that appear to attract only females, and those that attract both sexes, as well as nymphs when this has been tested (Table 1) [16,17,57,58]. The only exception is for Piezodorus hybneri (Westwood); its pheromone appears to be bifunctional, acting either as a sex or aggregation pheromone, depending on the time of the year [59,60]. In comparison, sex-aggregation pheromones have only been identified for a few species (Table 1).…”
Section: Vibratory and Pheromone Signals In Stink Bug Matingmentioning
confidence: 99%
“…Sex and aggregation pheromones have been identified in approximatively 50 species where the pattern of responses is divided between those that appear to attract only females, and those that attract both sexes, as well as nymphs when this has been tested (Table 1) [16,17,57,58]. The only exception is for Piezodorus hybneri (Westwood); its pheromone appears to be bifunctional, acting either as a sex or aggregation pheromone, depending on the time of the year [59,60]. In comparison, sex-aggregation pheromones have only been identified for a few species (Table 1).…”
Section: Vibratory and Pheromone Signals In Stink Bug Matingmentioning
confidence: 99%
“…132 Besides 118-121, smaller amounts of the unsaturated analogues 123-130 occur possessing a Z-double bond at the u-7 or the u-9 position. 133,134 Lactones 118,119,120,125,126,128,129, and 130 proved to be active in electrophysiological assays using coupled gas chromatography/mass spectrometry. 130 The results showed that large molecules such as the 25 membered ring lactone 129 are volatile enough to serve as a volatile signal.…”
Section: Larger Macrocyclic Lactonesmentioning
confidence: 99%
“…125 Field experiments showed attraction only in high doses. 126 Lactone 116 and macrolides 117, 118, and 119 are also constituents of the scent gland secretion of several male Heliconius butteries, i.e. H. melpomene, together with similar uand u-1 macrolides ranging from C 12 to C 20 .…”
Section: Larger Macrocyclic Lactonesmentioning
confidence: 99%
“…Male adults of P. hybneri attract conspecific adults of both sexes [3] via a pheromone comprising β-sesquiphellandrene (Sesq), (R)-15-hexadecanolide (R15), and methyl (Z)-8-hexadecenoate (Z8) [4]. These synthetic chemical mixtures attract conspecific adults, especially females in fields [5]. Our previous study [6] revealed that P. hybneri males produce the pheromone simultaneously with their development to sexual maturity, and that diapausing males produce no pheromone components; thus, the pheromone is likely to play a role in sexual communication.…”
Section: Introductionmentioning
confidence: 99%
“…The biological function or attractiveness of each pheromone components or its blends for P. hybneri is largely unknown. In fields, each P. hybneri pheromone component alone lacked the attractiveness, while three-component mixture was attractive to P. hybneri [5]. Leal et al [4] showed that the full three-component mixture was attractive more than the any binary mixtures in laboratory conditions, whereas the attractiveness of the different blend ratios has never been investigated.…”
mentioning
confidence: 99%